2019
DOI: 10.4062/biomolther.2018.202
|View full text |Cite
|
Sign up to set email alerts
|

7,8-Dihydroxyflavone Protects High Glucose-Damaged Neuronal Cells against Oxidative Stress

Abstract: Oxidative stress is considered a major contributor in the pathogenesis of diabetic neuropathy and in diabetes complications, such as nephropathy and cardiovascular diseases. Diabetic neuropathy, which is the most frequent complications of diabetes, affect sensory, motor, and autonomic nerves. This study aimed to investigate whether 7,8-dihydroxyflavone (7,8-DHF) protects SH-SY5Y neuronal cells against high glucose-induced toxicity. In the current study, we found that diabetic patients exhibited higher lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…Although the antioxidant enzyme activities, SOD and CAT, were not affected by drug administration, the lipid peroxidation was reduced. In a recent study made with neuronal cells, 7,8-DHF protected high glucose-damaged cell against oxidative stress (Cho et al 2019). Powerful antioxidant action of 7,8-DHF has been demonstrated in several studies against in scopolamine-induced oxidative stress (Chen et al 2014), glutamate-induced toxicity (Chen et al 2011), cerebral ischemia injury (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the antioxidant enzyme activities, SOD and CAT, were not affected by drug administration, the lipid peroxidation was reduced. In a recent study made with neuronal cells, 7,8-DHF protected high glucose-damaged cell against oxidative stress (Cho et al 2019). Powerful antioxidant action of 7,8-DHF has been demonstrated in several studies against in scopolamine-induced oxidative stress (Chen et al 2014), glutamate-induced toxicity (Chen et al 2011), cerebral ischemia injury (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The primary extracellular signal-regulated kinase (ERK) 2 (sc-1647) and phospho-ERK1/2 (sc-7383) antibodies were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA). The primary Actin (A2066) antibody was purchased from Sigma-Aldrich Chemical Company (St. Louis, MO, USA) [17].…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors did not provide direct causal evidence supporting BDNF/TrkB contributed to cardiac remodeling. Lately, another study found that 7,8-DHF protected neurons from high glucose-induced oxidative stress [ 53 ]. However, the potential role of 7,8-DHF in high glucose-induced cardiomyocyte injury and diabetic cardiomyopathy is undetermined.…”
Section: Role Of Bdnf/trkb In Vascular and Metabolic Diseasesmentioning
confidence: 99%